The effect of a mindfulness-based stress intervention on neurobiological and symptom measures in adolescents with early life stress: a randomized feasibility study - Zsofia P. Cohen; Kelly T. Cosgrove; Elisabeth Akeman; Sara Coffey; Kent Teague; Jennifer Hays-Grudo; Martin P. Paulus; Robin L. Aupperle; Namik Kirlic (BMC, 2021)
Abstract Background Early life stress (ELS) has been linked to poor mental and physical health outcomes in adolescence and adulthood. Mindfulness reduces symptoms of depression and anxiety and improves cognitive and social outcomes in both youth and adults. However, little is known whether mindfulness can mitigate against the adverse neurobiological and psychological effects of ELS. This study aimed to examine the feasibility of conducting a group mindfulness intervention in adolescents with ELS and provide preliminary indication of potential effects on stress-related biomarkers and mental health symptoms. Methods Forty adolescents were randomized to receive either eight sessions of Mindfulness-Based Stress Reduction for Teens in group format (MBSR-T; n = 21) or Treatment as Usual Control group (CTRL; n = 17). Outcomes were assessed at baseline and follow-up and included measures associated with neurobiological functioning (immune and endocrine biomarkers) and self-reported mental health (depressive) symptoms. Linear mixed effects models were used to assess the effects of group and time on these outcome measures. Results Sixteen of the 21 adolescents completed the intervention, attending an average of 6.5 sessions. The model examining cortisol responses to stress induction revealed medium effects trending toward significance (Cohen's d = .56) for anticipatory cortisol levels in the MBSR-T relative to CTRL groups. No significant effects were found in models examining C-reactive protein or interleukin 6 inflammatory markers. The model examining depressive symptoms revealed a medium effect for symptom reduction (Cohen's d = .69) in the MBSR-T relative to CTRL groups. Conclusions This study demonstrated feasibility of conducting a group-based MBSR-T intervention for adolescents with ELS. There was some evidence for efficacy on a symptom level with potential subtle changes on a biological level. Future larger studies are needed to determine the efficacy of group-based mindfulness interventions in this population. Trial registration Identifier # NCT03633903 , registered 16/08/2018.